Dissatisfied, uninformed or both? Democratic satisfaction, political knowledge and the acceptance of clientelism in a new democracy. Issue 2 (17th February 2022) - Gherghina, Sergiu; Saikkonen, Inga; Bankov, Petar
ABSTRACT: In many countries, voters are targeted with clientelistic and programmatic electoral offers. Existing research explores the demand side of clientelism, but we still know very little about what determines voters' acceptance of clientelistic and programmatic electoral offers. This article builds a novel theoretical framework on the role that democratic dissatisfaction and political knowledge play in shaping voters' acceptance of different types of electoral offers. We test the implications of the theory with a survey experiment conducted after the 2019 local elections in Bulgaria. Our results show that low-knowledge voters and those who are dissatisfied with the performance of democracy and democratic institutions are more likely to accept clientelistic offers from politicians. The findings contribute to the literature on electoral clientelism and political attitudes.